2019
DOI: 10.1073/pnas.1911570116
|View full text |Cite
|
Sign up to set email alerts
|

Spatial ecology of territorial populations

Abstract: Many ecosystems, from vegetation to biofilms, are composed of territorial populations that compete for both nutrients and physical space. What are the implications of such spatial organization for biodiversity? To address this question, we developed and analyzed a model of territorial resource competition. In the model, all species obey trade-offs inspired by biophysical constraints on metabolism; the species occupy nonoverlapping territories, while nutrients diffuse in space. We find that the nutrient diffusi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
(72 reference statements)
1
15
0
Order By: Relevance
“…Finally, the phenomena we observe are reminiscent of territorial resource competition seen in a variety of ecosystems at various scales [100]. Previous models have suggested that such effects play important roles in maintaining diversity [101,102]. Specifically, the barrier formation we observe is similar to gap formation that occurs during competition between plants [103,104].…”
Section: Discussionsupporting
confidence: 66%
“…Finally, the phenomena we observe are reminiscent of territorial resource competition seen in a variety of ecosystems at various scales [100]. Previous models have suggested that such effects play important roles in maintaining diversity [101,102]. Specifically, the barrier formation we observe is similar to gap formation that occurs during competition between plants [103,104].…”
Section: Discussionsupporting
confidence: 66%
“…Such models often require connections to an external meta-community to maintain long-term stability [26], lest random fluctuations will eventually drive finite systems toward lower diversity [27,28]. Many other mechanisms (which we cannot do justice to here) have also been proposed for maintenance of diversity in competitive ecosystems, including but not limited to: stochasticity and priority effects [29,30]; environmental variability [31]; models that encode specific relationships between species to maintain diversity [32] (including the classic rock-paper-scissors spatial game [11], cross-feeding [33][34][35][36][37], metabolic trade-offs [38][39][40], or cross-protection [41]); varied interaction models [42]; higher-order interactionsbeyond pairwise-that stabilize diversity [43][44][45][46]; and systems where evolution and ecological competition happen simultaneously [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the crossings of different growth contours take an extreme form in the substitutable-nutrient model with exact trade-offs, where all strategies intersect at the same chemical environment, enabling a flat fitness landscape for unlimited coexistence [27]. In subsequent works that assume non-exact trade-offs and spatial structure [42], or temporal variation in nutrient supply with immigration [57], a large number of species still coexist, demonstrating how a nearly-flat fitness landscape can promote diversity. Moreover, we also demonstrated that ecological or evolutionary adaptation towards a higher growth rate promotes the emergence of keystone species, which ultimately create a flat landscape for all species.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this system, once any pair of species with a mutual-invasion relationship constructs the steady-state chemical environment together, all species become effectively neutral. Subsequent works showed that with spatial structure [42], even non-exact trade-offs can lead to high species abundance by partially "leveling the playing field" among different metabolic strategies, showing the potential of a nearly-flat fitness landscape to promote biodiversity.…”
Section: Plos Computational Biologymentioning
confidence: 99%